'British is professional, American is urban': attitudes towards English reference accents in Spain. (15th April 2016) - Carrie, Erin
Abstract : The spread and diversification of English worldwide challenges the use of reference accents in EFL classrooms. Yet, learners often demonstrate greater recognition of, familiarity with and preference for inner‐circle varieties of English speech, especially Received Pronunciation (RP) and General American (GenAm). This paper investigates the attitudes of 71 university students in Spain towards these speech varieties. Using the verbal guise technique, it measures cognitive, affective and conative responses to speech stimuli. Qualitative comments, collected using questionnaires and interviews, help to interpret these evaluative responses. The findings suggest a desire to emulate RP, often associated with status and prestige, though greater solidarity and stronger affiliative feelings towards GenAm speakers. They highlight the complexity and dynamism of the language attitudes of EFL learners in the Spanish context.